Using Polycaprolactone Nanofibers for the Proof-of-Concept Construction of the Alveolar-Capillary Interface - Capandova, Michaela; Sedlakova, Veronika; Vorac, Zbynek; Kotasova, Hana; Dumkova, Jana; Moran, Lukas; Jaros, Josef; Antol, Matej; Bohaciakova, Dasa; Hampl, Ales (Journal of biomedical materials research. Part A, 2025)
The alveolar-capillary interface is the key functional element of gas exchange in the human lung, and disruptions to this interface can lead to significant medical complications. However, it is currently challenging to adequately model this interface in vitro, as it requires not only the co-culture of human alveolar epithelial and endothelial cells but mainly the preparation of a biocompatible scaffold that mimics the basement membrane. This scaffold should support cell seeding from both sides, and maintain optimal cell adhesion, growth, and differentiation conditions. Our study investigates the use of polycaprolactone (PCL) nanofibers as a versatile substrate for such cell cultures, aiming to model the alveolar-capillary interface more accurately. We optimized nanofiber production parameters, utilized polyamide mesh UHELON as a mechanical support for scaffold handling, and created 3D-printed inserts for specialized co-cultures. Our findings confirm that PCL nanofibrous scaffolds are manageable and support the co-culture of diverse cell types, effectively enabling cell attachment, proliferation, and differentiation. Our research establishes a proof-of-concept model for the alveolar-capillary interface, offering significant potential for enhancing cell-based testing and advancing tissue-engineering applications that require specific nanofibrous matrices.
Keywords: Polyesters; Proof of Concept Study; lidé; Tissue Scaffolds; plicní alveoly; tkáňové podpůrné struktury; polyestery; Basement Membrane; bazální membrána; nanovlákna; ověření koncepční studie; Humans; Tissue Engineering; Nanofibers; tkáňové inženýrství; Pulmonary Alveoli